Microstructure, Tribological and Strength Properties of the Surface Layer in Metal-Ceramic Composite Nano-Structured by Electron Irradiation; AIP Conference Proceedings; Vol. 1909 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2017 (AMHS’17) - Ovcharenko V. E. Vladimir Efimovich (2017, 2017)
Title screen